Charakteristick der Bibel / von August Hermann Niemeyer. - Niemeyer, August Hermann, 1754-1828. (Tufts University. Tisch Library., 2015)
Volume 3 of 5; 5 volumes ; 22 cm (8vo); Edition varies.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.